Experimental and Numerical Investigation of Recirculation Structures in Isothermal Swirling Coaxial Jet - Pattanshetti A.; Santhosh R.; Attar N. (My University, 2025)
Three-dimensional (3D) unsteady Reynolds-averaged Navier–Stokes (URANS) simulations are conducted in a coaxial swirling jet. Two distinct types of recirculation zones (RZ) relevant to coaxial swirling jets are considered based on the modified Rossby number Rom, which is known to represent the ratio of axial velocity deficit between two coaxial streams to the characteristic tangential velocity at the nozzle exit. The two flow states studied are Rom > 1 and Rom ≤ 1. The former is characterized by regions of high strain (especially in the shear layer between central and coaxial jet). It is found in this study that renormalization group ðRNGÞ k - E model is the suitable model for 3D URANS simulation of Rom > 1 flow state. This is attributed to the model’s ability to simulate flow regions that are heavily strained. The simulated results are compared with two-dimensional laser Doppler velocimetry measurements conducted as part of this study. For the flow states Rom ≤ 1; which are characterized by the dominance of radial pressure gradient arising due to rotational (swirling) effect over the pressure gradient due to axial velocity deficit, the Reynolds stress model (RSM) is found best to simulate the flow topologies and mean and turbulent quantities. The time-averaged results obtained from optimized turbulent models are employed to gain insights into the fluid mixing phenomenon in these RZs. The unsteady axial velocity fluctuations obtained from both experiments and URANS simulations are analyzed in the frequency domain to gain insights into dominant axial oscillations prevalent in RZs. Copyright © 2022 by ASME.